Sistem Pendukung Keputusan Dalam Penilaian Kinerja Karyawan Terbaik dengan Algoritma Simple Additive Weighting (SAW) - Arisantoso Arisantoso; Nanang Sadikin; Ahmad Fatih; Mochamad Sanwasih (STMIK Budi Darma, 2021)
The goal of this study is to implement the best employee selection decision support system (DSS) using simple additive weighting (SAW) methods. The advantage of a simple additive weighting method over other decision models is that SAW can choose the best alternative among several alternatives, also allowing for more accurate estimation because it is based on predetermined criteria and preference weights. The decision support system for the best performance performance assessment of employees is designed using an object-oriented approach that usecase diagrams. So that it makes it easier to design the system created, and implemented by using the PHP programming language with MySql database so that the calculation process can be stored computerized using the database. System testing results using blackbox testing get 100% results in accordance with system functionality testing, and Technology Acceptence Model test results get 85.41% results then Technology Acceptence Model prototype Is Excellent for decision support systems for the selection of the best employees